On the origins of the cartouche and encircling symbolism in Old Kingdom pyramids - Lightbody, David I., (Access archaeology., 2020)
This study suggests the development of the cartouche was closely related to the monumental encircling symbolism incorporated into the architectural designs of the Old Kingdom pyramids. By employing a new architectural style and a new iconographic symbol, the pharaoh sought to elevate his status above that of the members of his powerful court.